2006
DOI: 10.1007/s10286-006-0373-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of postural tachycardia syndrome: a comparison of octreotide and midodrine

Abstract: We assessed the potency of octreotide and midodrine, and their combination, in the treatment of the postural tachycardia syndrome (POTS) and orthostatic intolerance (OI). Nine patients with POTS and six patients with OI stood for up to 1 hour while their HR and BP were monitored. Patients received on separate days, midodrine 10 mg 1 hour before testing, octreotide 0.9 micro g/kg 8 minutes before testing or combination therapy. Standing time in the patients with POTS was 41.2 +/- 8.4 minutes and not improved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Successful strategies focused on improving orthostatic tolerance have concentrated on reducing the volume of blood in these compliant regions (Hoeldtke et al 2006;Hoeldtke et al 2007;Melchior et al 1996;Rowell 1986). We previously found that administration of octreotide acetate, a somatostatin analog whose vascular effects are largely confined to the splanchnic circulation, improved tilt table tolerance in healthy volunteers (Jarvis et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Successful strategies focused on improving orthostatic tolerance have concentrated on reducing the volume of blood in these compliant regions (Hoeldtke et al 2006;Hoeldtke et al 2007;Melchior et al 1996;Rowell 1986). We previously found that administration of octreotide acetate, a somatostatin analog whose vascular effects are largely confined to the splanchnic circulation, improved tilt table tolerance in healthy volunteers (Jarvis et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Although splanchnic hypervolemia during the post-prandial period is a well-recognized phenomena, it has only been recently documented that splanchnic hypervolemia occurs during orthostatic stress in patients with orthostatic syncope [12] and POTS [13]. This finding makes subcutaneous [7] and intramuscular octreotide theoretically attractive therapeutic options in patients with these conditions. We accordingly documented that octreotide LAR improved orthostatic tolerance in these patients and the hemodynamic benefits were associated with improvement in fatigue, dizziness and multiple other symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…Treatment is mostly symptom-oriented and includes methylphenidate, bupropion, octreotide, midodrine, and modafinil [5,7,25]. Co-occurrence of POTS and TCM falls far short of causal association.…”
Section: Discussionmentioning
confidence: 99%